THE EFFECT OF FUNDING ON THE PERFORMANCE OF THE GOVERNMENT SERVICE INSTITUTION: ANALYTICAL RESEARCH (World Economics and Finance Bulletin, 2022)
The research aims to show the role or extent of the impact of financing in its various forms on municipal performance before and after financial deficit through relying on the analytical research methodology of the research community represented by Directorate General of Municipalities and Directorate of Missan municipalities as a sample of research (13) municipal institutions for a period of (8) years, Considering the completion of final accounts of these years, which provides the necessary data for study, in addition the variation in quality and amounts of grants allocated to municipal institutions during these years, which gives a clearer and more comprehensive picture of the reality of allocations received by municipal institutions before and after financial crisis Using three financial analysis tools (horizontal, vertical, and percentage analysis). Among the statistical analysis tools (SPSS), the Pearson correlation coefficient was used (to calculate correlation between finance and municipal performance), and analysis of multiple linear regression coefficient. The researcher relied on financial data contained in official records and documents of municipal institutions studied. The main findings of the research are that municipal performance depends on availability of funding to support activities of municipal institutions. It depends on central budget to cover all financial needs and this exposes them to risk of facing the lack of financial resources .Central funding is characterized by fluctuation and instability in terms of its impact on external conditions and the general situation of state, while selffinancing is characterized by flexibility and ability to continue whenever more attention to confiscation and areas of diversity
Keywords: Financing; various; government; financial